VARIATION OF JAPANESE JACK MACKEREL (TRACHURUS JAPONICUS TEMMINCK & SCHLEGEL, 1884) POPULATION IN TONKIN GULF COMMON FISHING ZONE DURING 2006 - 2013 - Hai, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2015)
In the period 2006 - 2013, a total of 32 trawl surveys were conducted in the Common Fishing Zone (CFZ) between Vietnam and China in Gulf of Tonkin. A total of 1,060 trawl samplings (mesh size at cod end 2a = 30 mm) were conducted regularly in January, April, July and October from 2006 - 2013 with towing duration of one hour per haul on average. Japanese horse mackerel (Trachurus japonicus) frequently appeared in catch of the trawl samples with a frequency of 77.5% (821/1,060 hauls). Catch of Japanese horse mackerel contributed about 5% in the total trip catch, on average. Catch Per Unit Effort (CPUE) was highest in July and lowest in April. Standing stock biomass of Japanese horse mackerel was seasonally dependent with the phase of two-year drop and increase.